Patterns in State Funding of Public Higher Education: Demography, Ideology, Educational Attainment, and Trends - Gerhard Glomm; Manu Raghav (Global Labor Organization (GLO), 2024)
The affordability of public higher education and, by extension, public higher education funding, is an important concern to prospective students and their parents as well as to policymakers. Our study examines the allocation of constant dollar per-student state appropriations across four-year or higher public colleges and universities over the years from 2000-01 to 2021-22. Our main findings are that per-student constant dollar state appropriations for public four-year institutions decrease with the percentage of conservative state voters and increase with the percentage of state population under twenty-five years and the percentage of the state population over sixty-five years, the state sex ratio (defined as the number of males per 100 females), and the percentage of the population with a bachelor's degree or higher. Per-student constant dollar state appropriations continually and steadily decreased throughout this period. Most of our results on demography, ideology, and educational attainment are driven by non-R1 institutions. The time trends differ fundamentally between the R1 and the non-R1 institutions.
Keywords: I23; I22; H7; 330; State Appropriations; Public Higher Education Institutions; Higher Educational Finance; Education Funding